Application of SEBT on core training measurement on fin swimming athletes - Qu, P.; Wang, C.; Zheng, W. (Proceedings of the International Conference on Future Computer Science and Education, 2011, 2011)
The purpose of this study is to investigate the effect of core training on dynamic stability competency on elite fin swimming athletes by SEBT. The subjects in this study were 24 elite fin swimming athletes from Chinese national team, are randomly divided into two groups: core training group and traditional training group. The training planning was 50 minutes/session, 4 times/week for 8weeks. S-E-T is taken as main mean, and also Swiss ball supplemented with other core training methods were given to core training group, while traditional training group is given conventional lower back and abdomen strength training, such as V up and so on. We measured the changes of dynamic stability competency of the participants by SEBT both pre and post the whole training. The dynamic stability competency increased drastically followed the 8-weeks core training, and the difference between pre and post training was very significant (p<; 0.01). Moreover, core training group was superior to traditional training group and had extremely significant difference after 8-weeks training (p<;0.01). Eight weeks core training can significantly improve the dynamic stability of fin swimmers compared with conventional lower back and abdomen strength training. SEBT can show neuromuscular control (proprioception), lower body strength, and ROM thoroughly and accurately.